Epidemiological assessment of oral and maxillofacial hard and soft tissue injuries: a one-year survey in Amin hospital of Isfahan city - Zarean, Parichehr; Namin, Abolfath Hosseinzadeh; Zarean, Paridokht; Bashardoust, Nasrollah; Savabi, Ghazal (Journal of Stomatology, 2017)
Introduction. The increasing incidence of accidents expose individuals to a variety of traumas. With maxillofacial trauma being one of the most common and considering lack of reports on the incidence of maxillofacial injuries in Isfahan, the present study aimed to assess the oral and maxillofacial injuries in patients referred to Amin hospital in order to achieve better diagnostics, treatment and prevention of complications. Material and methods. In this descriptive cross-sectional study, the medical records of patients who sustained maxillofacial injuries and where referred to Amin hospital of Isfahan were evaluated within March 2015-2016. Hours, days and months of referral, duration of hospitalization, age, sex, marital status, cause of injuries, type and site of hard and soft tissue injuries, mean size of lacerations, related injuries and type of treatment plan were recorded. Result. The majority of patients were male (74%) and single (59/58%). Most subjects were in their twenties. Summer time on Thursdays and Saturdays between 6-12 PM were the most visited times. The patients mostly stayed 0-5 days in hospital. Injuries were mostly caused by road traffic accidents. The most common site of injuries was the nose (21/99%). In soft tissue injuries, lacerations were the most common with the longest ones in the forehead. Dental and orthopedic were the most related injuries. The most common bone fracture treatment was close reduction. Conclusion. Population’s geographic and cultural features can affect the incidence of maxillofacial injuries, which will in return affect the treatment plans. Therefore, considering these parameters would be useful for appropriate health care policy and management protocols in every society.